Wireless Connection between Guide Wires and Bone Cement: Extravasated Methyl Methacrylate Mimicking a Retained Guide Wire - Kevin C. Ching; Avinash Medsinge; Vikas Agarwal; Robert F. Short; Nikhil B. Amesur (Case Reports in Radiology)
We present the case of a 56-year-old double lung transplant recipient with chest pain who underwent an attempted endovascular retrieval of what was described as a retained guide wire in the azygos vein. After successfully grasping the tip, the object further migrated to the right pulmonary artery complicating the retrieval. It was realized that the “wire” was extravasated methyl methacrylate from a recent percutaneous kyphoplasty. This is believed to be the first report of attempted endovascular retrieval of extravasated methyl methacrylate in the azygos system. We include the details of this case and briefly review the current literature on the management of extravasated methyl methacrylate from vertebral augmentation procedures. Extravasated methyl methacrylate in the venous system is a common finding after vertebral augmentation procedures and any radiopaque stripe arising from a cemented vertebral body should be first described as probable cement leakage.